Mass Migration Process between Turkey’s Eastern Regions and Seaboard-Western Regions - Bakırtaş, Tahsin; Kandemir, Orhan (Eurasian Economists Association, 2010)
In the study, the aim is to analyze the economic causes of the migration phenomenon that is the most important problem of today’s Turkey, and to suggest different policy proposals for the solution of the problem. Within this frame, by accepting sixteen cities that receive high rates of migration according to arithmetical average of 2007-2008 and 2008-2009 periods indicated in the Address-Based Population Registration System as “center of attraction”, migration movements from eastern cities and from cities apart from eastern cities (western cities) to these sixteen cities of “center of attraction” were analyzed separately. In order to explain migration that oriented to centers of attraction, a multiple regression model that is convenient with international literature was formed. In this model, the number of enterprise that represents employment opportunity, the number of green card holders that represents poverty related to low income, the number of illiterates that represents lack of education and lastly the number of criminals that represents unrest were taken as independent variables. According to analysis results, independent variables that are used in the model explained migration process in both eastern cities and western cities as above 90%. On the other hand, when the coefficient rates of independent variables are examined, it was revealed that the most important determinant in economic migration is the employment opportunity. Consequently, making only income increasing social aids in regions where migration to other cities takes place is not sufficient; in addition to that, increasing employment opportunities is a healthier and a long-term solution.
Keywords: 2. Zero hunger; 11. Sustainability; 8. Economic growth; 1. No poverty; 16. Peace & justice; 12. Responsible consumption